Restructuring the Heart From Failure to Success: Role of Structural Interventions in the Realm of Heart Failure - Kir, Devika; Munagala, Mrudula (Frontiers in Cardiovascular Medicine, 2022)
Heart failure through the spectrum of reduced (HFrEF), mid-range (or mildly reduced or HFmEF), and preserved ejection fraction (HFpEF), continues to plague patients’ quality of life through recurrent admissions and high mortality rates. Despite tremendous innovation in medical therapy, patients continue to experience refractory congestive symptoms due to adverse left ventricular remodeling, significant functional mitral regurgitation (FMR), and right-sided failure symptoms due to significant functional tricuspid regurgitation (FTR). As most of these patients are surgically challenging for open cardiac surgery, the past decade has seen the development and evolution of different percutaneous structural interventions targeted at improving FMR and FTR. There is renewed interest in the sphere of left ventricular restorative devices to effect reverse remodeling and thereby improve effective stroke volume and patient outcomes. For patients suffering from HFpEF, there is still a paucity of disease-modifying effective medical therapies, and these patients continue to have recurrent heart failure exacerbations due to impaired left ventricular relaxation and high filling pressures. Structural therapies involving the implantation of inter-atrial shunt devices to decrease left atrial pressure and the development of implantable devices in the pulmonary artery for real-time hemodynamic monitoring would help redefine treatment and outcomes for patients with HFpEF. Lastly, there is pre-clinical data supportive of soft robotic cardiac sleeves that serve to improve cardiac function, can assist contraction as well as relaxation of the heart, and have the potential to be customized for each patient. In this review, we focus on the role of structural interventions in heart failure as it stands in current clinical practice, evaluate the evidence amassed so far, and review promising structural therapies that may transform the future of heart failure management.